GAYA PENGASUHAN PERMISIF DAN RENDAHNYA SOSIALISASI NILAI DALAM KELUARGA BERISIKO TERHADAP PENURUNAN KARAKTER REMAJA - Pasaribu, Ria Magdalena; Hastuti, Dwi; Alfiasari, Alfiasari (Jurnal Ilmu Keluarga dan Konsumen, 2013)
Parenting style and parents’ methods of socialization that examine the interaction between parents and child are the important factors toward adolescent’s quality. This research was aimed to analyze the influence of theparenting style and parents’ methods of socialization on character of high school students in Bogor City, West Java Province. This research was conducted in six schools representing public and vocational high schools, the sample of this research was 200 students consisted of 100 male and 100 female students. The samples criteria were grade X students and came from an intact family. The data was collected from May until June 2012. The result showed that there are positive correlations between: family income and father’s permissive/mother’sauthoritarian parenting styles; authoritative parenting style of both parents and methods of socialization of both parents; authoritative parenting style of both parents and adolescent’s character; and between methods of socialization of both parents and adolescent’s character. Negative correlations were found between: permissive parenting style of both parents and methods of socialization of both parents; and between permissive parenting style of both parents and adolescent’s character. Authoritative parenting style and methods of socialization of mothers positively influenced character of adolescents, while permissive parenting style of mothers negatively influenced adolescents’ character.